Pengaruh Penggunaan Media Pembelajaran Daring Telekonferensi Terhadap Minat Belajar Pai Siswa Kelas Xi Di Sman 1 Bayah - Irpan Hakim; Sri Nurul Milla; Retno Triwoelandari (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
Learning media is one of the factors that influence student learning success. One of the learning media is teleconference media, this teleconference media helps educators in conveying material to students more effectively. This study aims to determine the effect of using teleconference online learning media on students' interest in PAI learning. This research method uses quantitative methods with a quasi-experimental design of the nonequivalent control group design type. Researchers obtained data from 65 students by conducting experiments on the experimental class and the control class through a post-test. The results showed that; 1) The use of online learning media teleconference is in the medium category. 2) The results of the research in the experimental class and control class after receiving treatment, the average value of the experimental class is 44.09 and the control class is 39.94. 3) there is a significant influence between the use of online learning media teleconference on interest in learning Islamic Religious Education obtained from the Independent Sample T Test, it is known that the significance value of student interest = Sig. (2-tailed) 0.000 <0.05 so Ho is rejected, so that the results of the post-test measurement of interest in learning have a significant effect. To increase student interest in online learning, educators should understand well in choosing the right and effective online media, especially in Islamic Religious Education subjects, so that later students/students have a good interest in learning. Keywords: Online Learning, Teleconferencing Media and Student Interests.